Study on the pore structure characteristics and damage constitutive model of sandstone under freeze-thaw conditions - Ma, Junzu; Jin, Jiaxu; Wu, Pengfei; Qin, Zhifa; Jia, Baoxin (Frontiers in Earth Science, 2023)
Rocks in northwest China are often affected by the combined action of freeze-thaw and load erosion. Therefore, in order to better understand the mechanical properties of rocks in seasonal frozen areas and the meso-damage caused by freeze-thaw erosion, uniaxial compression tests, electron microscope scanning tests, X-ray diffraction tests (XRD) and mercury intrusion tests (MIP) were carried out on five sandstone samples with different freeze-thaw times, and the mechanical parameters and meso-damage characteristics of sandstone samples with different freeze-thaw times were obtained. Fractal theory was used to analyze the change in pore volume of sandstone after freeze-thaw cycles. Finally, the damage constitutive equation under the coupling action of freeze-thaw damage and load was established based on Lemaitre’s equivalent effect variation criterion. The results showed that the type of sandstone is a porous coarse-grained sandstone. With the increased freeze-thaw times, the compressive strength and cohesion of sandstone gradually decreased, and the closed pores in sandstone gradually connected, leading to the visible internal macroscopic cracks. Affected by freeze-thaw times, the volume proportion of large pores (100 µm-1000 µm) in sandstone gradually increased, while the volume proportion of micropores (0.05 µm-100 µm) gradually decreased. With the increased freeze-thaw times, the fractal dimension of pore volume decreased from 1.94 to 1.59. The theoretical curve can better fit the characteristic points of the stress-strain curve, which can further reveal the damage mechanism of sandstone under the coupling effects of freeze-thaw and load. The minimum error between the peak point of the experimental curve and the theoretical curve is 3.3%.